Escavações: a metalinguagem nos contos de Virgínia Woolf - Rodrigues, Tereza Cristina Tófolis (2012)
This dissertation aims to examine the English writer Virginia Woolf attempts of apprehending, through the handling and of the reflection on the written word, all the complexity that her sensibility inferred in the human experience. For that, we sought to follow the tracks left by the frequent metalinguistics discussion that the author establishes in her work concerning the nature and the possibilities of the narrative. This work accompanies different moments in the career of Woolf through the analysis of four of the stories compiled in The complete shorter fiction, organized by Susan Dick: \"Memoirs of the novelist\", \"The Mark on the Wall\", A Summimg Up\" and \"The Searchlight\". Through them and the investigation of the use of literary procedures considered innovative in the end of the XX Century for Woolf, this dissertation observes her literary production searching out the authorial voice. We understood that the prominence to the concept of the metalanguage, that sends to the capacity of the language to bend on herself, makes possible the problematization of the inherent subjects to the literary speech in aspects that interested the writer a lot, but also all the readers. Trying, Virginia Woolf reinvigorates the writing, at the same time she meditates about their possibilities. Tracking her paths in the stories, this work creates a type of dialogue with the English writer on subjects as the sense transitivity, the changing aspect of the word and, mainly, the anguish in getting to capture the inexpressible.